Overview of age-related morphological changes in the fovea capitis - Phruksachat Singsuwan (2018)
© 2018 Japan Health Sciences University & Japan International Cultural Exchange Foundation. Objective: Age estimation is a crucial task of human skeletal identification for forensic anthropologists. Previous studies attempt to develop age estimation method from the several parts of the human skeleton in both single and multiple age indicators. The morphology of the fovea capitis on the proximal femur is affected by age-related changes and the fovea capitis is also often well preserved due to its protected position within the acetabulum, making it potentially valuable for age estimation in a forensic context. This paper will explain the overview on age-related changes in the fovea capitis. Conclusion: This paper will be a starting point for developing an age estimation method for use in combination with the other age indicators of the os coxa including the acetabulum.